Analysis of SAKTI User Satisfaction Using the Importance Performance Analysis (IPA) Method - Amin, Nur Yaqin; Su’un, Muhammad; Selong, Abbas (Invoice : Jurnal Ilmu Akuntansi, 2024)
The Ministry of Finance has officially launched the Institutional Level Financial Application System (SAKTI) for all work unit of Ministry/Institutional in 2022. Seeing the diverse characteristics of work unit throughout Indonesia, there will potentially be many problems that users will face. During the piloting stage from 2015, various problems were found that made end users unsatisfied. This study aimed to find out: (1) the level of satisfaction of SAKTI users after it was officially implemented in all work unit of Ministry/Institutional; (2) the attributes that need to be improved and maintained in SAKTI based on 5 End User Computing Satisfaction (EUCS) variables, namely Content, Accuracy, Format, Ease of Use, and Timeliness. This study used primary data through a survey of 107 respondents as sample from 78 work unit of KPPN Makassar II. The data were analyzed using importance performance analysis (IPA). The results of this study showed that: (1) based on the t test, analysis of the level of conformity and analysis of the performance-expectation gap based on the 5 EUCS variables, SAKTI's quality was good in meeting user expectations with user satisfaction level of 96%. Gap analysis shows that all EUCS variables are negative (<0), which means that the quality of SAKTI's performance has not met user expectations; (2) based on the Cartesian diagram mapping, there are 12 top priority attributes that must be implemented according to the expectations of SAKTI users and their performance must be improved and maintained.